FORENSIC PSYCHIATRIC CARE OF INTELLECTUALLY DISABLED OFFENDERS DIMINISHES RISK FOR CRIMINAL RECIDIVISM - FINNISH REGISTER-BASED STUDY - AULIKKI AHLGRÉN-RIMPILÄINEN, MAIJA LINDGREN, PETTERI JOELSSON, NINA LINDBERG (Psychiatria Fennica)
ABSTRACT Objectives: The focus of this study was on the reoffending rate and patterns of severe violent crimes committed by persons with intellectual disability (ID) in the Finnish context of forensic psychiatry. Materials and methods: 178 persons with ID (ICD-10 diagnosis code F70-79) were identified from the national register of forensic psychiatric examination (FPE) reports in Finland in 1990-2015. The reoffence data was derived from the Police crime register up until 2020. During the follow-up, missing or deceased persons were excluded from the study. Sociodemographic factors, all diagnoses, types of main crimes and reoffences (homicide, assault, sexual crime, arson/sabotage, property or other crimes), and the conclusions of FPE (criminal responsibility and placement after FPE in homes, prison or involuntary psychiatric or disability care) were collected. Results: A total of 56% of the subjects reoffended during the follow-up. They were younger than the non-reoffenders and mostly diagnosed with mild ID. The majority (60%) of the subjects were sentenced to prison after the completed FPE. Prison-placed offenders with ID had an eightfold risk of reoffending compared to those who had been in psychiatric care after the FPE. Compared to the groups with involuntary treatment, prison-placed offenders with ID committed and reoffended most in homicides and assault category crimes The delay of committing a new crime was the longest in the psychiatric treatment group. Involuntary treatment, especially long-term psychiatric care, and older age at the time of the index crime were protective factors against reoffending. Conclusions: Prison sentence after FPE possibly increases risk of criminal recidivism. The high reoffending rate indicates that the needs and risks of perpetrators with ID should be better assessed during the FPE, and afterwards be taken into account in the court decision and social care procedures.